Urban agrarian reform: opportunities and challenges for land rights among low-income communities - Suhadi, Suhadi; Niravita, Aprila (Legality : Jurnal Ilmiah Hukum, 2024)
Agrarian reform has typically focused on the redistribution of land in rural areas, specifically targeting farmers and agricultural tracts of land. This study explores the potential for agrarian reform in urban settings and the challenges facing low-income individuals in acquiring land rights essential to adequate housing. Using statutory and theoretical perspectives demonstrates that ample opportunities still exist for urban agrarian reform to take hold via the expropriation of state-owned land and land whose rights have lapsed. Public land that has not been dedicated as a waqf or even recognized as government property and historic land rights where the building rights expired and without any application to extend those rights present empirical reform opportunities. Despite these opportunities, urban land rights remain a contested space. Many poor people live on untitled land because such a thing is considered disputed by public authorities. Conflicts arise from the physical duration of inhabitants' occupation, which is in severe contrast to claims found with entities holding either outdated or inadequate property documentation. The official bodies, particularly the Land Office, are hesitant to issue land certificates due to these conflicts. The uniqueness of this research lies in its focus on urban land reform and its implications for the poor, thus highlighting a gap in existing literature that focuses largely on rural settings. This important research study depends on the emerging need for appropriate and certain housing options in cities. The importance of this study to the discipline is that it fosters the application of national land law principles, namely equity, legal certainty, and practicality, to disputes over urban land, providing a framework for a fairer distribution of land rights.